2009
DOI: 10.1073/pnas.0900343106
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous expression of Hras G12V induces developmental defects and neoplasms with copy number imbalances of the oncogene

Abstract: We developed mice with germline endogenous expression of oncogenic Hras to study effects on development and mechanisms of tumor initiation. They had high perinatal mortality, abnormal cranial dimensions, defective dental ameloblasts, and nasal septal deviation, consistent with some of the features of human Costello syndrome. These mice developed papillomas and angiosarcomas, which were associated with Hras G12V allelic imbalance and augmented Hras signaling. Endogenous expression of Hras G12V was also associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 41 publications
5
157
0
Order By: Relevance
“…Subsequently, several groups reported that RAS V12 and mutant RAF proteins act mitogenically or, conversely, drive cells into senescence as a function of increasing expression levels (Woods et al 1997;Guerra et al 2003;Deng et al 2004;Tuveson et al 2004;Sarkisian et al 2007;Chen et al 2009). Some of these observations, and the fact that commonly used culturing conditions differ markedly from those in intact tissue and presumably act as a further stressor, initially caused some skepticism about a physiological role for senescence.…”
Section: Cellular Senescence As a Pathophysiological Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, several groups reported that RAS V12 and mutant RAF proteins act mitogenically or, conversely, drive cells into senescence as a function of increasing expression levels (Woods et al 1997;Guerra et al 2003;Deng et al 2004;Tuveson et al 2004;Sarkisian et al 2007;Chen et al 2009). Some of these observations, and the fact that commonly used culturing conditions differ markedly from those in intact tissue and presumably act as a further stressor, initially caused some skepticism about a physiological role for senescence.…”
Section: Cellular Senescence As a Pathophysiological Phenomenonmentioning
confidence: 99%
“…For instance, increased expression of activated RAS genes is a common feature of human tumors (Elenbaas et al 2001;Johnson et al 2005;Okamura et al 2006;Chen et al 2009) that can be associated with the conversion from benign to malignant tumors (Quintanilla et al 1986;Finney and Bishop 1993;RodriguezPuebla et al 1999). Amplification of HRAS V12 is common in human Spitz nevi, which rarely progress to malignancy (Maldonado et al 2004), probably representing the best available evidence of high levels of a mutant RAS gene in a growth-arrested benign neoplastic lesion.…”
Section: Cellular Senescence As a Pathophysiological Phenomenonmentioning
confidence: 99%
“…The existing mouse model based on an oncogenic p.G12V mutation does not exhibit myocyte disarray [Fig. 10, Schuhmacher et al, 2008], which may mean that the mutant is not a completely comparable animal model [Chen et al, 2009] …”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…There were no reports of microdissection of the conduction system to validate Mori et al's [1996] observation of ''degeneration of the conduction system'' in which abnormalities of the conduction pathways led to the atrioventricular node. The existing mouse model does not exhibit tachycardia [Schuhmacher et al, 2008;Chen et al, 2009]. Atrial tachycardia may be a functional consequence of diastolic dysfunction in adults with HCM where increased filling pressure is associated with increased atrial stretch leading to dysrhythmia [Brembilla-Perrot et al, 1997].…”
Section: Arrhythmiamentioning
confidence: 99%
See 1 more Smart Citation